Pengaruh Literasi Halal, Dan Tingkat Harga Terhadap Keputusan Pembelian Produk Skincare - Bahrotul Dwi Safitri; Ahmad Syahrizal; Ogi Saputra (STIKes Ibnu Sina Ajibarang, 2023)
This research aims to determine the influence of halal literacy and price levels on purchasing decisions for skincare products. The method used in this research is a quantitative research method. The data collection technique is carried out by filling out a questionnaire. The sample used was 96 respondents where the sample was taken using non-probability sampling techniques. Based on the results of the research that has been carried out, it can be concluded that the results of the research show that there is a simultaneous influence between the level of halal literacy and the price level on purchasing decisions with Fcount of 26.435, this value is greater than Ftable, namely 3,09 with a significance of 0.000. The determination test shows how much influence the halal literacy variables and price levels have on purchasing decisions, an R square value of 0.326 or 100 x 0.326 = 32.6% is obtained. So the contribution of halal literacy and price levels is 32.6% while the remainder (100% - 32.6% = 67%) is influenced by other factors.